Exploring Indonesia government outbreak response: Misinformation of public officials in handling of Covid-19 Pandemic - Nugroho, Catur; Wulandari, Astri; Muna, Fatimath; Nastain, M. (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
The Covid-19 outbreak started in March 2020, and the Indonesian government has taken a long time to respond to it. With different ambiguous statements, public leaders contributed to the disruption of knowledge concerning the Covid-19 pandemic. Therefore, the study aims to investigate the communication strategy of Indonesia’s government in response to the early Covid-19 pandemic in March 2020. This study uses a qualitative method that analyzes news text from online media. The data collection technique in this research is a literature study. The source of this research data comes from statements by four Indonesian ministers regarding the Covid-19 outbreak from online media. The goal of this study is to understand the narrative in online media concerning Indonesian public officials' response to COVID-19 by analyzing the word frequency using NVIVO 12 Plus software. Findings from this study indicate that numerous issues with the utilization and dissemination of information about the COVID-19 pandemic demonstrate a lack of maturity and caution on the part of the government and media. Indonesia’s government could not provide excellent and precise information that followed the community's expectations regarding the pandemic. Indonesian public officials contributed to misinformation regarding the Covid-19 epidemic when dealing with the pandemic by providing ambiguous, incorrect, and misleading information.